Crystal structure and Hirshfeld surface analysis of dimethyl (1R*,3aS*,3a1R*,6aS*,9R*,9aS*)-3a1,5,6,9a-tetrahydro-1H,4H,9H-1,3a:6a,9-diepoxyphenalene-2,3-dicarboxylate - Kseniia A. Alekseeva; Pavel V. Raspertov; Sevim Türktekin Çelikesir; Mehmet Akkurt; Flavien A. A. Toze; Elena A. Sorokina (Acta Crystallographica Section E: Crystallographic Communications, 2019)
The title diepoxyphenalene derivative, C17H18O6, comprises a fused cyclic system containing four five-membered rings (two dihydrofuran and two tetrahydrofuran) and one six-membered ring (cyclohexane). The five-membered dihydrofuran and tetrahydrofuran rings adopt envelope conformations, and the six-membered cyclohexane ring adopts a distorted chair conformation. Two methyl carboxylate groups occupy adjacent positions (2- and 3-) on a tetrahydrofuran ring. In the crystal, two pairs of C—H...O hydrogen bonds link the molecules to form inversion dimers, enclosing two R22(6) ring motifs, that stack along the a-axis direction and are arranged in layers parallel to the bc plane.